The new cryptography. - Sterling, Bruce (Fantasy & Science Fiction)
Focuses on cryptography, the science of ancient writing. Ancient places where cryptography was used; Use of cryptography during the war; Impact of technology on the context of the use of cryptography; Development of encryption as a business in the 1990s; Types and classes of cryptography.